2020
DOI: 10.1103/physrevmaterials.4.085201
|View full text |Cite
|
Sign up to set email alerts
|

Red luminescence in H-doped βGa2O3

Abstract: The effects of hydrogen incorporation into -Ga2O3 thin films have been investigated by chemical, electrical and optical characterization techniques. Hydrogen incorporation was achieved by remote plasma doping without any structural alterations of the film; however, Xray photoemission reveals major changes in the oxygen chemical environment. Depth-resolved cathodoluminescence (CL) reveals that the near-surface region of the H-doped Ga2O3 film exhibits a distinct red luminescence (RL) band at 1.9 eV. The emerge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Thus, the Raman spectra were measured on the low energy side flank of a red fluorescence emission, the intensity of which is increasing with temperature in H 2 . In literature, the presence of red luminescence has been related to oxygen vacancies, [54] but also recently to hydrogen dissolved in Ga 2 O 3 [55] . Bulk processes are indeed involved, because this luminescence can only be removed by annealing in O 2 at 650 °C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the Raman spectra were measured on the low energy side flank of a red fluorescence emission, the intensity of which is increasing with temperature in H 2 . In literature, the presence of red luminescence has been related to oxygen vacancies, [54] but also recently to hydrogen dissolved in Ga 2 O 3 [55] . Bulk processes are indeed involved, because this luminescence can only be removed by annealing in O 2 at 650 °C.…”
Section: Resultsmentioning
confidence: 99%
“…In literature, the presence of red luminescence has been related to oxygen vacancies, [54] but also recently to hydrogen dissolved in Ga 2 O 3 . [55] Bulk processes are indeed involved, because this luminescence can only be removed by annealing in O 2 at 650 °C. Dong et al [56] performed calculations describing the formation of oxygen vacancies on Ga 2 O 3 as a function of oxygen treatment and concluded that the presence of oxygen increases their formation energy.…”
Section: Chemcatchemmentioning
confidence: 99%
“…Huynh et al in ref. [40] discussed in detail the effect of red luminescence in hydrogen doped gallium oxide. Inclusion of hydrogen in the -Ga 2 O 3 structure decreases layer resistance from 10 10  / sq to 4•10 8  / sq at 300 K. A high-valence gallium oxide with a binding energy 533.4 eV if hydrogen doping is present, H-radicals are absorbed in -Ga 2 O 3 and form strong bonds with oxygen atoms.…”
Section: Luminescent Devicesmentioning
confidence: 99%
“…Luminescence of β-Ga 2 O 3 generally exhibits mainly UV (3.2-3.6 eV), blue (2.8-3.0 eV) and green (2.5 eV) lines, [34][35][36] but a red (1.7-1.9 eV) line has also been reported. [37][38][39] The UV line as been ascribed to recombination between free electrons and self-trapped holes (STHs), while the other lines relate to donor acceptor pair recombination involving a range of intrinsic (e.g. V O , V Ga , Ga i ) or extrinsic (e.g.…”
Section: Optical Propertiesmentioning
confidence: 99%